An Unsuspected Finding of t(9;22): A Rare Case of Philadelphia Chromosome-Positive B-Lymphoblastic Lymphoma. (18th September 2017) - Boddu, Prajwal; Yin, C. Cameron; Kanagal-Shamanna, Rashmi; Tang, Guillin; Thakral, Beenu; Kadia, Tapan; Konopleva, Marina; Jabbour, Elias; Jain, Nitin
Abstract : While rare, cases of isolated extramedullary disease of B-cell Lymphoblastic Lymphoma (B-LBL) without morphologic bone marrow involvement have been described. In this report, we illustrate the case of an elderly gentleman who presented with isolated testicular and vertebral LBL involvement but had no morphologic bone marrow involvement. The initial plan of treatment was to treat along the lines of Philadelphia negative B-ALL/LBL. During this time, fluorescence in situ hybridization (FISH) and PCR testing for BCR-ABL1 rearrangements were being performed on the marrow specimens as a part of routine diagnostic workup. While the FISH returned negative, PCR testing unexpectedly detected BCR-ABL1 fusion transcripts at a low level of 0.48%. Given their presence, we performed FISH for BCR/ABL1 rearrangement in both testicular and L5 vertebral specimens which were 80–90% positive. He subsequently received rituximab, hyper-CVAD, and dasatinib, along with prophylactic intrathecal prophylactic chemotherapy. The patient achieved a prolonged remission but eventually relapsed, 4 years later. Had it not been for this fortuitous discovery, the patient would not have been treated with tyrosine kinase inhibitors. We emphasize that FISH and PCR testing for BCR-ABL1 rearrangement are integral to arriving at an accurate diagnosis and should be routinely tested on B-LBL biopsy specimens.